Effect of metal back geometry on the stability of cementless acetabular cup - Abdul Kadir, Mohammed Rafiq; N. , Kamsah; M. , Salim (Springer Berlin Heidelberg, 2008)
The long-term success of cementless total hip arthroplasty depends on the initial stability of its acetabular component. To achieve adequate stability for possible osseointegration, biomedical engineers have incorporated features such as fins, spikes, threads and screws. Others use pressfitting technique by having a component with a diameter larger than the reamed acetabular cavity. All the techniques have been incorporated with varying degrees of success. Loosening of the component still occurs especially in younger patients. In this study, two design features of acetabular cup — the fins and the screws — were analysed using three-dimensional finite element method. Another model without any macrofeature was used as control. A left human pelvis was reconstructed from CT datasets and the acetabulum was virtually reamed to simulate preparation of the bone bed. Non-linear contact analyses were performed using physiological gait as the boundary condition. An in-house experimentally validated micromotion algorithm was used to measure the micromotion at the bone-implant interface. Results showed that an acetabular cup without any fixation features produced micromotion up to a maximum of 3mm. The introduction of fins and screws reduced the micromotion abruptly to 5microns, with the screws provide better stability than the fins.